Disorder of purine metabolism in the etiopathogenesis of urate nephrolithiasis - S. I. Vorotyntsev; A. I. Bilai; I. M. Bilai (Zaporozhye State Medical University, 2023)
Urinary stone disease (USD) is a polyetiological urological disease caused by both exogenous and endogenous factors, including hereditary ones. It is characterized by the appearance of stones in the kidneys and urinary tract, and a tendency to relapse, often with a severe course. Almost 25 % of stones consist of uric acid (UA). The leading role in the pathogenesis of urate nephrolithiasis (UN) is played by disorders of purine metabolism, which are characterized by the development of hyperuricemia (HU) and hyperuricuria. The aim of the work is to review modern literary sources on the role of purine metabolism disorders in the etiopathogenesis of UN. Results. The development of UN depends on the constancy of the acidic urine pH, as well as on a decrease in diuresis, HU and hyperuricuria. UA is the final metabolite of purine metabolism and the main stone-forming substance in patients with UN. HU develops both due to uncompensated disorders of purine metabolism with a decrease in renal secretion and intestinal uricolysis (excretion pathway) and excessive intake of purine bases in the body and their increased synthesis in vivo (metabolic pathway). Citric acid, as one of the main metabolites of the tricarboxylic acid (TCA) cycle, is connected through the corresponding substrates to the formation of purines and the metabolite of amino acid metabolism, glutamine. TCA is connected to the cycles of urea, glyoxylate and purine bases through α-ketaglutaric acid. It is a substrate of citric acid, and it affects the synthesis of glutamate, which combines with ammonia to form glutamine, used in the cycle of purine synthesis. Conclusions. The role and diagnostic value of purine metabolism upsets, disorders of the TCA (citric acid), amino acid metabolism (glutamine), the activity of xanthine oxidase is a key enzyme in purine synthesis which passes through TCA with the participation of its metabolite α-ketaglutarate, have been established. TCA is bound to glutamine, rich in nitrogen, which is necessary for the synthesis of purine bases.